PSII-20 Effects of aerobically exposed corn silage treated with medium chain fatty acids on rumen fermentation in vitro. (30th November 2020) - Arzola-Alvarez, Claudio; Ruiz-Barrera, Oscar; Castillo-Castillo, Yamicela; Ontiveros, Marina; Fonseca, Mozart; Jones, Barbara W; Smith, William B; Hume, Michael; Beier, Ross C; Harvey, Roger; Poole, Toni L; Anderson, Robin; et al.
Abstract: Medium chain fatty acid (MCFA) treatment of aerobically exposed silage during feed-out is a potential strategy to prevent growth of spoilage and pathogenic microbes. To evaluate the effects of feeding MCFA-treated silage on the rumen fermentability, we incubated 0.02 g of overnight air-exposed corn silage that had been treated individually without or with (0.75% wt/wt) C6, C8, C10 or C12 or with equal proportion mixtures of C6:C8:C10:C12 or C8:C10 with 10 mL freshly collected ruminal fluid. Additions were made while flushing with CO2 and tubes (3 tubes/treatment) were then capped and sealed. After 24 h incubation at 39 o C, headspace gases and fluid volatile fatty acids were measure using gas chromatography techniques. Results from a completely randomized analysis of variance revealed higher hydrogen accumulations (P < 0.05) only in incubations containing silage treated with the C8:C10 MCFA mixture when compared to controls, with mean ± SD concentrations (µmol/mL incubation fluid) being 2.19 ± 1.6 versus 0.08 ± 0.04, respectively. Treatment effects were not observed (P > 0.05) on accumulations (µmol/mL) of methane (13.25 ± 2.5), acetate (19.66 ± 5.6), propionate (7.27 ± 2.0), butyrate (12.36 ± 2.7) or stochiometric estimates of amounts of hexose fermented (41.39 ± 9.7), although the acetate:propionate ratios of incubations of silage treated with C8 or the C8:C10 mixture were higher (P < 0.05) than those of untreated controls (3.46 ± 0.7, 3.46 ± 0.5 and 2.35 ± 0.1, respectively). Consequently, correspondingly estimates of fermentation efficiency, calculated based caloric energy values of amounts of acetate, propionate and butyrate relative to glucose, were slightly lower (P < 0.05) for the incubations of silage treated with C8 and the C8:C10 mix compared to controls (74.36 ± 1.1, 74.82 ± 0.2 and 76.55 ± 0.3 %, respectively). Results reveal little negative effect of MCFA treatment on ruminal fermentability of silage.